The 8th European Conference on Antennas and Propagation (EuCAP 2014) 2014
DOI: 10.1109/eucap.2014.6902236
|View full text |Cite
|
Sign up to set email alerts
|

Compact structure of band-pass filter integrated with Defected Microstrip Structure (DMS) for wideband applications

Abstract: This paper presents compact structure of bandpass filter integrated with Defected Microstrip Structure (DMS) to produce band-pass and band reject response simultaneously. The filter design based upon g0 short-circuited stubs structures of 7 th degree. The narrow notch responses produced by DMS was introduced at a frequency of 5.2 GHz in order to reject any undesired signals which may interfere with the wideband communication systems. The design was simulated and fabricated on a Roger Duroid RO4350 with a thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In order to solve the problem of floor energy leakage, a defective microstrip structure is proposed. [20,21], which can also generate slow wave characteristics. In [22], the authors proposed a microstrip notch filter based on electromagnetic bandgap structure, which realized a high rejection broadband filter.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the problem of floor energy leakage, a defective microstrip structure is proposed. [20,21], which can also generate slow wave characteristics. In [22], the authors proposed a microstrip notch filter based on electromagnetic bandgap structure, which realized a high rejection broadband filter.…”
Section: Introductionmentioning
confidence: 99%
“…A number of techniques to design ultra-wideband bandpass filters with notched bands have been studied [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The notch bands are generated by introducing a resonance unit, such as a stepped impedance resonator (SIR) [ 2 , 3 ] and multi-mode resonator (MMR) [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of adopting stepped impedance resonator or multi-mode resonator is that the size of the notch filter is too large and the transmission zero cannot be flexibly adjusted. The stop-band function is achieved by introducing defect ground structure (DGS) [ 10 , 11 ] and defect microstrip structure (DMS) [ 12 , 13 ]. Defect ground structure can effectively reduce the size of the filter, but it is difficult to obtain good broadband and sharp skirt selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Band-pass filters play a role important part. It is regarded as one of most usable structures in microwave engineering [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra wideband (UWB) system has dozens of advantages for both academia and industry such as low power, high speed communication system and high precision ranging [4]. A number of the research wideband BPFs have been reported based on different methods and design methodologies from [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%